Financial Distress Analysis Using The Altman Z-Score Method For Retail Companies During The Covid-19 Pandemic - Ratnawaty Marginingsih (Institute of Computer Science (IOCS), 2022)
The retail industry is one of the sectors hardest hit by the impact of the Covid-19 pandemic. This condition has resulted in a number of large retail companies in Indonesia experiencing financial distress to the point of announcing that they experienced losses and could no longer survive. The purpose of this study was to analyze financial distress in retail companies during the covid-19 pandemic. In this research, the type of descriptive quantitative research is used. The sampling technique used purposive sampling technique and the type of data used secondary data. The data collection method uses the financial statements of retail sector companies with hypermarket, supermarket and minimarket businesses that have been published for the 2017-2020 period. Data analysis used the first Altman Z-Score discriminant ratio model. The results of the study show that from 2017-2019 most issuers are in the non-distress category or not bankrupt, except for HERO which is in a gray area condition. Then for 2020 the issuers of MPPA, RANC, AMRT remain in a non-distress condition, while the issuers of RALS and MIDI shift to the condition of the gray area, issuers of HERO are experiencing a setback by being in a state of distress or experiencing financial difficulties.